THE ROLE OF ENGLISH TRAVEL MATERIALS IN PROMOTING RESPONSIBLE TOURISM BEHAVIOR IN TRA QUE VEGETABLE VILLAGE - Nguyen , Linh Ngoc; Phan , Thi Thanh Binh (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2026)
Tourism is a crucial driver of Vietnam’s economy, with sustainable tourism receiving increasing attention. Among Vietnam’s ecotourism destinations, Tra Que Vegetable Village (TQVV) in Hoi An stands out for its cultural heritage and ecological significance. While sustainability initiatives are in place, challenges remain in effectively promoting responsible tourism behaviors. This study examines the role of English-language travel materials (ETMs), including guidebooks, brochures and online articles on travel websites in fostering sustainable tourism practices in TQVV. Adopting a mixed-method approach, the research integrates document analysis, surveys with international tourists, and interviews with local stakeholders. Findings reveal that while ETMs help raise awareness of sustainability issues, they often lack persuasive messaging, interactive features, and engaging narratives. The study underscores the need for clearer sustainability-focused content, the integration of digital tools, and more visually compelling materials. Based on these insights, practical recommendations are proposed to enhance ETMs, including improved storytelling techniques, QR code integration, and culturally relevant sustainability messages. These findings provide valuable guidance for local tourism authorities and content creators in strengthening responsible tourism communication and supporting the sustainable development of TQVV.